Analisis Pengelolaan Barang Milik Daerah Kota Sibolga - Deliana, Deliana; Lubis, Musliadi; Hidayah Napitupulu, Ilham (Journal of Accounting and Finance Management, 2024)
This study aims to analyze the management of regional assets in the City of Sibolga, identify the challenges faced in the management process, and determine the steps that need to be taken to ensure more orderly asset administration. The operationalization of the variables in this study is based on the management of regional assets according to Minister of Finance Decree (KMK) Number 288/KMK.06/2023. Data collected using interviews, observations, and documentation, with key informants including the Head of the Agency, Head of Budgeting Division, Head of Assets Division, and Head of Treasury and Accounting Division. The qualitative data management technique follows the Miles and Huberman model, which includes data reduction, data presentation, and conclusion drawing and verification. The findings indicate that the management of regional assets in Sibolga City faces various challenges such as inaccurate asset data, lack of supervision and control, suboptimal coordination between OPDs, and insufficient asset security and maintenance. To address these issues, it is recommended that the Sibolga City Government enhance human resource capacity, develop an integrated asset management information system, optimize the budget for asset maintenance and security, and improve supervision and control over the use of fixed assets